Alienation and Affectivity: Beauvoir, Sartre and Levinas on the Ageing Body. Issue 1 (1st June 2019) - Lennon, Kathleen; Wilde, Anthony
Abstract : In this article, we explore Beauvoir's account of what she claims is an alienated relation to our ageing bodies. This body can inhibit an active engagement with the world, which marks our humanity. Her claims rest on the binary between the body-for-itself and the body-in-itself. She shares this binary with Sartre, but a perceptive phenomenology of the affective body can also be found, which works against this binary and allows her thought to be brought into conversation with Levinas. For Levinas, the susceptibility of the body is constitutive of our subjectivity, rather than a source of alienation. If we develop Beauvoir's thought in the direction of his, an ontological structure is suggested, distinct from Sartre – a structure which makes room for her pervasive attention to affectivity.